Integrated approach to strategic planning in public institutions - Bivainis, Juozas; Tunčikienė, Živilė (Journal of Business Economics and Management, 2007)
Planning of actions for implementation of institution’s strategic decisions is one of the most complicated, on the other hand, the weakest in methodic provision complex objectives of strategic planning. Considering the local target of this phase of the strategic planning cycle to set the best ways to take the right directions in development of the scope of activity of an institution, a well‐reasoned composition of such a complex objective is as follows: generating action plan alternatives, defining the evaluation criteria of the alternatives and forming a combination of criteria, analysis and evaluation of the action plan alternatives, adopting a plan. The structure of an action plan for implementing institution’s strategic decisions arose the necessity to identify two‐level objectives for drawing up the plan as well as the specific sequence of objective fulfilment in an analysed complex. The specifics of each level was evaluated in our proposals for improvement of the planning of the implementation of institution’s strategic decisions based on the analysis of the results of progressive experience. First Published Online: 14 Oct 2010